Effect evaluation of a novel dehumidification structure based on the modified model. (1st March 2018) - Zhang, Guojie; Wang, Liang; Zhang, Sen; Li, Yimin; Zhou, Zhongning
Highlights: The modified model is developed to predict the condensing flow. NDS is presented to decrease the nucleation rate and liquid mass fraction. Based on NDS, IDS that can be easily manufactured is presented. The dehumidification effect of NDS and IDS is discussed. Abstract: In the course of energy conversion, steam turbine is one of the most important equipment, but the wet steam at the low-pressure stage will cause losses. The losses caused by condensing flow not only reduce the efficiency of steam turbine but also influence reliability. This paper firstly numerically investigated the Dykas cascade using the modified model, and compared with the experimental data. The results showed that the modified model had an enormous advantage in predicting the condensing flow. Besides, the advantage was obvious in calculating the pressure distribution of the blade and shock angle emerged in the blade trailing edge. Secondly, a novel dehumidification structure was proposed and the effect was calculated and discussed. The result showed that the novel structure had a positive effect on reducing the nucleation zone and the liquid mass fraction. Besides, the influence of different passage diameters was investigated, the conclusion can be drawn: both the liquid mass fraction of the outlet and the nucleation zone decrease with the increment of the passage diameter. Finally, an improved dehumidification structure which can be easily manufactured was presented and the structure with different φ was calculated. The results showed that when φ = 0, the dehumidification efficiency was remarkable, and the structure can be easily manufactured. However, the decrement of the liquid mass fraction was inconspicuous with the further increment of φ .